Hedging Efficiency of Indian Commodity Futures: An Empirical Analysis. Issue 1 (June 2017) - Gupta, Shashi; Choudhary, Himanshu; Agarwal, D.R.
This article examines the hedge ratio and hedging effectiveness in agricultural (castor seed, guar seed) and non-agricultural (copper, nickel, gold, silver, natural gas and crude oil) commodities traded in National Commodity and Derivative Exchange (NCDEX) and Multi Commodity Exchange (MCX), respectively. Constant and dynamic hedge ratios are estimated by using ordinary least square (OLS), vector autoregression (VAR), vector error correction model (VECM) and vector autoregressive-multivariate generalized autoregressive conditional heteroskedasticity model (VAR-MGARCH). The results of constant as well as dynamic hedge ratios reveal that the Indian futures market provides higher hedging effectiveness in case of precious metal (65–75 per cent) compared to industrial metal and energy commodities (less than 50 per cent). Hedging effectiveness for castor seed and natural gas is even lower than 10 per cent. This study concluded that VECM and VAR-MGARCH both are providing higher hedging although VECM is providing the highest hedge ratio. It has been found that the next to near month futures provide better hedging effectiveness as compared to near month futures for crude oil and silver. It is recommended that the policy makers should pay attention towards the number of delivery centres, standard of quality of underlying assets and transaction costs in spot market.